Gaya Kepemimpinan Religius Katolik pada Yayasan Pendidikan Katolik Keuskupan Amboina (Suatu Kajian Multi Situs) - Antonius Heatubun; Marianus Muharli Mua; Andrew C. Rattu; Theodorus Pangalila (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
Abstrak This research examines the Catholic religious leadership style at Siwa Lima Vocational School, Tourism Vocational School and Sanata Karya High School located in Langgur, Southeast Maluku, to reveal and know four things: Style, spirituality, characteristics and the impact of Catholic religious leadership implemented in the three educational units mentioned above. The research was carried out using observation, interview and documentation techniques as well as the symbols that appeared on the research subjects. The results of the study show that Catholic religious who lead educational institutions, in addition to following Jesus' leadership model, are also imbued with monastic spirituality which is lived and lived by every religious in the monastic community. The leadership that is carried is believed to be a gift from God and not merely a trust given by the Foundation. Leadership style as a servant, shepherd and caretaker is a leadership model that influences and inspires members with life examples and spiritual authority, which builds an educational unit into a community of love or school of love. The spirituality of the Sacred Heart of Jesus, Our Lady of the Sacred Heart and John Maria Vianey greatly influences the way of thinking, feeling and acting of religious leadership in three educational units; a spirituality lived and lived by Catholic religious based on an intimate relationship with Jesus through prayer and the Eucharist. The quality of Catholic religious leadership based on this relationship has a concrete impact on: exemplary, discipline, selfless work, spirit of service, respect for each person, cooperation are the values that are fought for.